De novo pathogenic DNM1L variant in a patient diagnosed with atypical hereditary sensory and autonomic neuropathy. Issue 10 (1st September 2019) - Tarailo‐Graovac, Maja; Zahir, Farah R.; Zivkovic, Irena; Moksa, Michelle; Selby, Kathryn; Sinha, Sunita; Nislow, Corey; Stockler‐Ipsiroglu, Sylvia G.; Sheffer, Ruth; Saada‐Reisch, Ann; Friedman, Jan M.; van Karnebeek, Clara D. M.; et al.
Abstract: Background: Profiling the entire genome at base pair resolution in a single test offers novel insights into disease by means of dissection of genetic contributors to phenotypic features. Methods: We performed genome sequencing for a patient who presented with atypical hereditary sensory and autonomic neuropathy, severe epileptic encephalopathy, global developmental delay, and growth hormone deficiency. Results: Assessment of the variants detected by mapped sequencing reads followed by Sanger confirmation revealed that the proband is a compound heterozygote for rare variants within RETREG1 ( FAM134B ), a gene associated with a recessive form of hereditary sensory and autonomic neuropathy, but not with epileptic encephalopathy or global developmental delay. Further analysis of the data also revealed a heterozygous missense variant in DNM1L, a gene previously implicated in an autosomal dominant encephalopathy, epilepsy, and global developmental delay and confirmed by Sanger sequencing to be a de novo variant not present in parental genomes. Conclusions: Our findings emphasize the importance of genome‐wide sequencing in patients with a well‐characterized genetic disease with atypical presentation. This approach reduces the potential for misdiagnoses. Abstract : Family pedigree of patient with variants in RETREG1 and DNM1L and Table with overlapping clinical phenotype of our patient compared to patients with either RETREG1 or DNM1L pathogenic variants.